Therapeutic Targeting of HIV Reservoirs: How to Give T Cells a New Direction - Yang, Hongbing; Wallace, Zoë; Dorrell, Lucy (Frontiers in Immunology, 2018)
HIV cannot be cured by current antiretroviral therapy (ART) because it persists in a transcriptionally silent form in long-lived CD4+ cells. Leading efforts to develop a functional cure have prioritised latency reversal to expose infected cells to immune surveillance, coupled with enhancement of the natural cytolytic function of immune effectors, or ‘kick and kill’. The most clinically advanced approach to improving the kill is therapeutic immunisation, which aims to augment or re-focus HIV-specific cytolytic T cell responses. However, no vaccine strategy has enabled sustained virological control after ART withdrawal. Novel approaches are needed to overcome the limitations of natural adaptive immune responses, which relate to their specificity, potency, durability and access to tissue reservoirs. Adoptive T cell therapy to treat HIV infection was first attempted over two decades ago, without success. Since then, progress in the field of cancer immunotherapy, together with recognition of the similarities in tumour microenvironments and HIV reservoirs has reignited interest in the application of T cell therapies to HIV eradication. Advances in engineering of chimeric antigen receptor (CAR)-transduced T cells have led to improved potency, persistence and latterly, resistance to HIV infection. Immune retargeting platforms have incorporated non-neutralising and broadly neutralising antibodies to generate Bispecific T cell Engagers (BiTEs) and Dual-Affinity Re-Targeting proteins (DARTs). T cell receptor engineering has enabled the development of the first bispecific Immune-mobilising monoclonal T Cell receptors Against Viruses (ImmTAV) molecules. Here we review the potential for these agents to provide a better ‘kill’ and the challenges ahead for clinical development.